CONTRIBUTIONS OF THE INTERNET TO THE ACADEMIC DEVELOPMENT OF UNIVERSITY BUSINESS EDUCATION UNDERGRADUATES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The need to ensure effective use of the internet by university students necessitated thisstudy to determine the contributions of internet to the academic development ofuniversity business education undergraduates in Anambra State. One researchquestion guided the study and two null hypotheses were tested. Survey researchdesign was used. Population was 647, university business education undergraduatesin Anambra State of the 2015/2016 academic session. Purposive sampling techniquewas used to draw a sample size of 156 (63 male and 93 female students). Instrumentfor data collection was a 5 – point rating scale structured questionnaire which wasduly validated by three experts and its reliability tested using Cronbach Alpha tocheck internal consistency of the items which yielded 0.69 coefficients. Data wereanalyzed using the arithmetic mean while z-test and ANOVA were used to test the nullhypotheses at 0.05 level of significance. Findings revealed that internet contributes toacademic development of university business education undergraduates. It was foundalso that gender and institution ownership did not significantly affect the respondents’response. Therefore, the researcher concluded that the internet is of immense benefitto the overall development of students. Based on the findings and conclusion of thestudy it was recommended among others that Government, through curriculumplanners should incorporate internet literacy into undergraduate programmes inorder to educate students on the risks and benefits of Internet use.
Keywords: Internet, Development, Academic Development, Business Education